Digital transformation of population administration: Enhancing data accessibility in local communities - Ozzi Suria; Putri Taqwa Prasetyaningrum; Irfan Pratama (University of Merdeka Malang, 2025)
This community service initiative addresses the need for an efficient population administration system in RT3/RW3, Rejowinangun Utara Village, Magelang, where several key issues hinder effective data management. These problems include manual record-keeping with logbooks, which may increase the risk of errors and data loss, limited accessibility to population information, and challenges in adopting digital technology due to limited technical knowledge and infrastructure. To resolve these problems, this activity is conducted in four phases: data gathering, system development, evaluation, and user training. During the data-gathering phase, discussions with the community leader and the collection of family record data were conducted to identify specific needs and challenges. The system development phase focused on creating a user-friendly web-based Population Administration System (PAS) tailored to these requirements. In the evaluation phase, the system was tested and refined based on feedback from the community leader to ensure functionality and usability. The user training phase provided hands-on experience to the community leader, enabling independent use of the system for managing data and generating demographic summaries. The implementation of PAS successfully transformed administrative processes into digital and improved data accessibility for the local community.